Generic affinities of African house snakes revised: a new genus for Boodon erlangeri (Serpentes: Elapoidea: Lamprophiidae: Lamprophiinae) - Tiutenko, Arthur; Koch, Claudia; Pabijan, Maciej; Zinenko, Oleksandr (Salamandra, 2022)
Lamprophis erlangeri is a lamprophiid snake endemic to moist montane forest remnants and formerly forested areas in the south and south-west of the Ethiopian highlands. Its vernacular name ‘Ethiopian House Snake’ is a result of century-long speculations about the generic placement of this species. New molecular and morphological data brought evidence that it has been misplaced in both genera of ‘African house snakes’, Lamprophis and Boaedon. A new genus is described to accommodate L. erlangeri. It represents a sister clade to the Western and Central African genera Bothrophthal-mus and Bothrolycus from which it differs by general body form and proportions, head shape, number of preocular scales, absence of loreal pits, maxillary dentition as well as by a number of cranial features. The type locality of the type species of the new genus, originally ‘Somaliland’, is restricted in this paper to Abera in Ethiopia. Lamprophis abyssinicus, the second Ethiopian endemic in this genus is assigned again to the genus Pseudoboodon on a basis of similar external morphology and cranial osteology. In the course of this revision of systematic affinities in Lamprophis and Boaedon, also the status of the genus Alopecion, considered to represent a junior synonym of these genera, is revalidated. It is reinstated as a valid monotypic genus, to include L. guttatus, a South-African species with similarly turbulent taxonomic history as of L. er-langeri. Cranial osteology of L. erlangeri, L. abyssinicus, and L. guttatus is analysed for the first time. Morphological, ecological and behavioural characters of the related genera Alopecion, Boaedon, Bothrolycus, Bothrophthalmus, Lamprophis, Lycodonomorphus, Pseudoboodon, and of the new genus are reviewed and compared.
CRIS-Team Scopus Importer:2022-11-18
Keywords: Alopecion annulifer; Boaedon abyssinicus; Boaedon erlangeri; Boaedon guttatus; Boaedontini; cranial osteology; Lamprophis abyssinicus; Lamprophis guttatus; molecular genetics; morphology; osteology; Pseudoboodon; skull; Squamata; systematics; taxonomy